352 Updated clinical data from the squamous cell carcinoma of the head and neck (SCCHN) expansion cohort of an ongoing Ph1/1b Study of eganelisib (formerly IPI-549) in combination with nivolumab. (10th December 2020) - Cohen, Ezra; Postow, Michael; Sullivan, Ryan; Hong, David; Yeckes-Rodin, Heather; McCarter, Jerry; Zizlsperger, Nora; Kutok, Jeffery; O'Connell, Brenda; Page, Kara; Roberts, Jennifer; Zhang, Halle; et al.
Abstract : Background: Eganelisib is a first-in-class, oral, selective PI3K-γ inhibitor. Preclinically, eganelisib reprograms macrophages/myeloid derived suppressor cells (MDSCs) from an immune-suppressive to an immune-activating phenotype and enhances efficacy of checkpoint inhibitors. Efficacy of eganelisib + nivolumab in patients with SCCHN resistant to immediate prior anti-PD(L)1 therapy is presented. Methods: IPI-549-01 (NCT02637531 ) evaluates eganelisib in advanced solid tumors, as monotherapy and in combination with nivolumab. The combination expansion dose was eganelisib 40 mg QD PO + nivolumab 240 mg Q2W IV. Combination expansion cohorts include SCCHN patients resistant to immediate prior anti-PD(L)1 therapy. Safety, preliminary clinical activity, PK, and correlative study of blood and tumor biopsy samples were mandated. Results: As of June 1, 2020, 180 patients were treated with eganelisib + nivolumab including 21 with SCCHN.The most common (>20% of patients) treatment-emergent adverse events in patients treated with eganelisib + nivolumab (N = 180) were fatigue (34.4%), increased AST (30.0%), increased ALT (26.7%), nausea (25.0%), pyrexia (25.0%), anemia (22.8%), decreased appetite (20.6%), and cough (20.6%). 85 (47.2%) patients experienced at least 1 treatment-emergent serious adverse event (SAE) and 19 (10.6%) had a treatment-related SAE. There were no treatment-related grade 5 adverse events as assessed by investigators. Preliminary data from the SCCHN cohort show that in the efficacy-evaluable population which includes all patients (n=20) who had at least 1 post-baseline response assessment or discontinued treatment due to disease progression, the overall response rate (ORR, ie. CR [complete response] or PR [partial response] per RECIST v1.1) is 10.0%, the disease control rate (DCR, ie. CR, PR, or SD [stable disease]) is 45.0%, and the clinical benefit rate (CBR, ie. CR, PR, or SD of at least 24 weeks from first treatment) is 25.0%, per RECISTv1.1. For patients that received ≤ 2 lines of prior systemic therapy (n=11), the ORR is 20.0%, the DCR is 40.0%, and the CBR is 30.0%. In total, there are 2 patients with PR (duration of response 1.6–9.3 months) and 3 with SD for greater than 6 months' treatment duration. Translational data including T cell proliferation in peripheral blood as well as markers of inflammation in baseline biopsy of PR patient will be presented. Conclusions: Eganelisib + nivolumab demonstrates an acceptable safety profile and preliminary clinical activity in patients with SCCHN who were resistant to immediate prior anti-PD(L)1 therapy. Updated clinical and translational data will be presented. Ethics Approval: The study was approved by WIRB, Study Number 1188591 and IRB Tracking Number: 20180297.